Using Various Fish Processing Techniques to Maintain Flesh Quality and Shelf Life: An Updated Review - Aljizani, Nouf; Shafi, Manal (Journal of King Abdulaziz University-Meteorology Environment and Arid Land Agriculture Sciences, 2024)
fish and fish products are crucial for human health, providing high-quality proteins, essential vitamins, minerals, and healthy polyunsaturated fatty acids. Furthermore, the great nutritional importance of these substances has been linked to numerous health benefits extending from prenatal development of the fetus to puberty .However, fish can deteriorate quickly after harvesting due to external environmental factors such as water quality (waste that turns into ammonia, nitrate, nitrite, pH, amount of dissolved oxygen, and temperature) and internal physiological factors such as microbes and bacteria, which increases the chance of their deterioration and loss of nutritional value. Therefore, it is essential to use techniques for aquaculture fish that are constantly evolving, focusing on the type and condition of the fish and applying appropriate techniques for farmed fish, considering the duration of transport. In addition, there are various techniques used in the preservation of aquaculture fish, including traditional techniques such as salting, drying, smoking, and pickling or marinating; non-traditional fish processing techniques include cooling, freezing, and vacuum packaging. Also, to determine fish freshness such as sensory characteristics, microbial analyses, physical and chemical evaluations. Fish processing techniques include methodologies and procedures used from harvest until reaching the consumer in its final form. This review investigates the most important preservation techniques used for fish and their impact on overall quality. In addition, it aims to achieve sustainable production with nutritional content, improve profitable productivity, and reduce negative health impacts on consumers and fear about the nutritional safety of food to achieve human in line with the Kingdom's Vision 2030's two pillars of a thriving economy and society.